Value Chain as Tool of Strategic Management in Agro-Industrial Complex - A. M. Nekhlanova (Вестник Российского экономического университета имени Г. В. Плеханова, 2021)
Analyzing organization competitiveness by production costs is an important analytical step for units of agroindustrial complex (AIC). Such importance can be explained by specific features of markets, where AIC units operate: produce is uniform and standardized or poorly differentiated, price competition plays the essential role, therefore organizations with low costs are leaders on market. In this situation one of the most important parameters of strategic standing of the organization is its capability to compete by costs. Topicality of using the value chain is stipulated by importance of managing processes of raising competitiveness by costs and realizing strategy in general. The article studies practical and methodological issues of strategic analysis of production costs. It shows results of empirical research on managing processes of forming costs in AIC units and identifies key problems that can impact their successful development in the long run. Special attention was paid to changing approaches to managing processes of forming costs and potential profit, the shift of searching for opportunities of competitiveness by costs from internal environment to outer one. Recommendations on using value chains in AIC strategic management on state level were worked out. It was shown that effective cooperation of state and private AIC units could promote attainment of strategic goals of AIC development.